The Implementation of the UMMI Method in Qur'anic Learning at Al Imam Islamic School Junior High, Bogor - Aniska Thohiroh; Akhmad Kharis Kurniawan; Neneng; Retno Ayu Atikah Dewi; Imas Maemunah; Suprihatin (Journal of Curriculum and Pedagogic Studies (JCPS), 2025)
Qur’anic education holds a central role in Islamic educational institutions, serving not only as a compulsory subject but also as a foundation for students’ religious understanding, spiritual awareness, and moral development. The UMMI Method has emerged as a structured approach that integrates tartil-based recitation, tajwid application, and student-centered repetition to enhance Qur’an reading skills. This study explores the implementation of the UMMI Method at Al Imam Islamic School Junior High in Bogor, focusing on teaching strategies, student engagement, and the method’s impact on students’ Qur’anic reading abilities. Using a qualitative field study approach, data were collected through classroom observations, interviews, and document analysis. Findings reveal that the UMMI Method is applied systematically with daily structured sessions, grouping students by proficiency levels, and employing certified teachers to ensure consistent instruction. The method significantly improves students’ fluency, accurate articulation (makhraj), tajwid comprehension, and overall recitation quality. It also addresses common challenges such as motivation and material retention. In conclusion, the UMMI Method is an effective strategy for enhancing Qur’anic learning at the junior high level and offers valuable insights for Islamic educators aiming to improve the quality of religious education in formal school settings